Gambaran Penerapan Prinsip Andragogi dalam Performansi Widyaiswara pada Kegiatan Pendidikan dan Pelatihan - Saprianto, Dedi; Solfema, Solfema (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the success of the widyaiswara in implementing the training given to participants at the Padang religious education and training center. The purpose of this study was to see the application of the andragogical principle in widyaiswara performance in the field to help develop a positive, open and flexible attitude, display a passionate attitude, and manage the behavior of training participants. This type of research is descriptive quantitative. Total population of 90 people with a sample of 45 people. The sampling technique is by random sampling. The technique used in data collection is a questionnaire, while the tool used in data collection is a list of statements. The data analysis technique uses the percentage formula. The results of the research show that the application of the andragogical principle in widyaiswara's performance in the field of developing positive attitudes, being open and flexible, showing a strong attitude, and managing the training participants' behavior are categorized very well, this can be seen from the high percentage of very good and good.